Aplikasi Bio-Ekologi Makrobenthos sebagai Indikator Tingkat Kesuburan Tambak - Muhammad, Fuad; Hidayat, Jafron Wasiq; Mukid, M. Abdul (JURNAL SAINS DAN MATEMATIKA, 2013)
Makrobenthos that live in the mangrove forest can be used to predict the role or contribution of mangrove ecosystems as a source of natural food for the environment. The aims of research to determine the structure, composition, abundance, diversity makrobenthos of the mangrove ecosystem. The study was conducted by comparing the community structure makrobenthos in pond ecosystem with mangrove vegetation constituent . The location of this study include three areas , Mangunharjo ( Semarang), Surodadi ( Demak ) andÂ  Pasarbangi. The result can shows makrobentos species composition is dominated by gastropods ( 18 species) , Bivalvia ( 13 species ) , Polychaeta ( 3 types ) , and crustaceans ( 2 types ) . Cerithium and Littorina scabra is a type that has a high density of the mangrove ecosystem . There are differences in the abundance and diversity of plankton and makrobenthos at three study sites. In general Pasarbangi Coast has the highest abundance and diversity . Macrozoobenthos community structure in mangrove ecosystems that exist in the three study sites in a stable state , species diversity and distribution of the number of individuals of each type of uniform . Pasarbangi area with mangrove vegetation polyculture farms , have high primary productivity . This shows the level of primer productivity at the site is also high. Â  Keywords: community structure, macrobenthos, pond ecosystem